An Automated Approach to Examining Pausing in the Speech of People With Dementia. (9th July 2020) - Sluis, Rachel A.; Angus, Daniel; Wiles, Janet; Back, Andrew; Gibson, Tingting (Amy); Liddle, Jacki; Worthy, Peter; Copland, David; Angwin, Anthony J
Dementia is a common neurodegenerative condition involving the deterioration of cognitive and communication skills. Pausing in the speech of people with dementia is a dysfluency that may be used to signal conversational trouble in social interaction. This study aimed to examine the speech-pausing profile within picture description samples from people with dementia and healthy controls (HCs) within the DementiaBank database using the Calpy computational speech processing toolkit. Sixty English-speaking participants between the ages of 53 and 88 years (Mage = 67.43, SD = 8.33; 42 females) were included in the study: 20 participants with mild cognitive impairment, 20 participants with moderate cognitive impairment, and 20 HCs. Quantitative analysis shows a progressive increase in the duration of pausing between HCs, the mild dementia group, and the moderate dementia group, respectively.